Respiratory virus infections in hospitalized children and adults in Lao PDR. Issue 6 (25th June 2013) - Sentilhes, Anne‐Charlotte; Choumlivong, Khamla; Celhay, Olivier; Sisouk, Thongchanh; Phonekeo, Darouny; Vongphrachanh, Phengta; Brey, Paul; Buchy, Philippe
<x xml:space="preserve">Abstract</x> Background Acute respiratory infections are an important cause of morbidity and mortality worldwide, with a major burden of disease in developing countries. The relative contribution of viruses in acute lower respiratory infections (ALRI) is, however, poorly documented in Lao PDR. Objective The objective of this study is to investigate the etiology of ALRI in patients of all ages in two hospitals of Laos. Methods Multiplex PCR/RT‐PCR methods were used to target 18 major common respiratory viruses. Between August 2009 and October 2010, samples from 292 patients presenting with ALRI were collected. Results and conclusion Viruses were detected in 162 (55%) samples. In 48% (140/292) of the total ALRI cases, a single virus was detected while coinfections were observed in 8% (22/292) of the samples. The most frequent viruses were rhinovirus/enterovirus (35%), human respiratory syncytial virus (26%), and influenza viruses (13%). Parainfluenza viruses were detected in 9%, adenovirus in 6%, human metapneumovirus in 4%, coronaviruses (229E, NL63, OC43, HKU1) in 4%, and bocavirus in 3% of ALRI specimens. Most viral infections occurred in patients below 5 years of age. The distribution of viruses varied according to age‐groups. No significant correlation was observed between the severity of the disease and the age of patients or the virus species. This study provides the description of viral etiology among patients presenting with ALRI in Lao PDR. Additional investigations are required to better understand the clinical role of the different viruses and their seasonality in Laos.